2021
DOI: 10.3389/fphys.2020.633721
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Pro12Ala Polymorphism on the PPARy2 Gene With the Body Composition of Practitioners of Cyclic Exercises

Abstract: This study aimed to verify the association between the genotypic of the receptor gene activated by peroxisome proliferators gamma 2 (PPARy2) and the body composition and the specific indicators of adiposity in practitioners physical exercises, considering nutritional intake, age, and training load as influencing factors. It was conducted a cross-sectional study with 335 adults (47.9 ± 12.7 years, 138 men, body mass index/BMI = 27.0 ± 4.9 kg/m2), practitioners of aerobic exercises in cyclical modalities (runnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…However, some studies ( 124 – 126 ) have come to conflicting conclusions. da Silva et al ( 124 ) demonstrated that CC homozygotes had significantly higher BMI and WHR compared to CG heterozygotes among Brazilian adult men. A similar finding was observed in teenagers from Northern Mexico, and the researchers noted that G allele carriers of the rs1801282 polymorphism exhibited significantly lower overweight/obesity phenotype (BMI Z -score) frequency than CC homozygotes ( 125 ).…”
Section: Mechanisms Underlying the Associations Between Pparγ Gene Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies ( 124 – 126 ) have come to conflicting conclusions. da Silva et al ( 124 ) demonstrated that CC homozygotes had significantly higher BMI and WHR compared to CG heterozygotes among Brazilian adult men. A similar finding was observed in teenagers from Northern Mexico, and the researchers noted that G allele carriers of the rs1801282 polymorphism exhibited significantly lower overweight/obesity phenotype (BMI Z -score) frequency than CC homozygotes ( 125 ).…”
Section: Mechanisms Underlying the Associations Between Pparγ Gene Po...mentioning
confidence: 99%
“…The association between the rs1801282 polymorphism and BMI was validated by two meta-analyses which concluded that G allele carriers had significantly higher BMI and higher prevalence of obesity than the subjects with CC genotype ( 122 , 123 ). However, some studies ( 124 – 126 ) have come to conflicting conclusions. da Silva et al ( 124 ) demonstrated that CC homozygotes had significantly higher BMI and WHR compared to CG heterozygotes among Brazilian adult men.…”
Section: Mechanisms Underlying the Associations Between Pparγ Gene Po...mentioning
confidence: 99%